2015
DOI: 10.1093/inthealth/ihv070
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to violence predicts poor educational outcomes in young children in South Africa and Malawi

Abstract: BackgroundViolence during childhood may affect short and long-term educational factors. There is scant literature on younger children from resource poor settings.MethodsThis study assessed child violence experiences (harsh punishment and exposure to domestic or community violence) and school enrolment, progress and attendance in children attending community-based organisations in South Africa and Malawi (n=989) at baseline and at 15 months' follow-up, examining differential experience of HIV positive, HIV affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 43 publications
2
35
0
3
Order By: Relevance
“…The role of different types of violence in predicting child outcomes in this sample has been explored in detail (Sherr et al ; Skeen et al ). In these analyses, the additional effect of poor caregiver mental health and its relationship with HIV was further explored.…”
Section: Discussionmentioning
confidence: 99%
“…The role of different types of violence in predicting child outcomes in this sample has been explored in detail (Sherr et al ; Skeen et al ). In these analyses, the additional effect of poor caregiver mental health and its relationship with HIV was further explored.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 64% of all adolescents aged 15 to 18 in South Africa currently experience two or more forms of violence in their lifetime, while 35.4% experience five or more forms of violence (Leoschut & Kafaar, ). Further, socio‐economic disadvantage, educational exclusion, and exposure to violence all pose a risk to educational progress (Herrero Romero, Hall, Cluver, Meinck, & Hinde, unpublished data; Pieterse, ; Sherr et al ., ). For instance, results from a recent cross‐sectional analysis of 4,747 youths aged 14–22 showed that repeated exposure to physical abuse at home was associated with school dropout and lower maths academic achievement (Pieterse, ).…”
Section: Introductionmentioning
confidence: 97%
“…Kabiru and colleagues found that adolescent girls aged 11-15 years who had experienced violence had lower expectations of achieving their aspirations compared to those who had not experienced violence [5]. A study conducted in Malawi and South Africa showed that exposure to violence has an impact on school enrolment and performance [7].…”
Section: Introductionmentioning
confidence: 99%